2021
DOI: 10.3390/ani11020401
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenol Supplementation in Food Producing Animals: Effects on the Quality of Derived Products

Abstract: The growing interest in producing healthier animal products with a higher ratio of polyunsaturated to saturated fatty acids, is associated with an increase in lipoperoxidation. For this reason, it is essential to attenuate oxidative deterioration in the derived products. Natural antioxidants such as polyphenols represent a good candidate in this respect. The first part of the review highlights the occurrence, bioavailability, and the role of polyphenols in food-producing animals that, especially in intensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 231 publications
2
75
1
2
Order By: Relevance
“…The replacement of growth promoters such as β-agonist and antibiotic growth promoters has been a great challenge for the meat industry for several years. Phytochemical compounds have been proposed as a natural alternative [ 27 , 28 ]. However, few phytochemicals have shown positive or at least similar effects to those triggered by traditional promoters on growth performance characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The replacement of growth promoters such as β-agonist and antibiotic growth promoters has been a great challenge for the meat industry for several years. Phytochemical compounds have been proposed as a natural alternative [ 27 , 28 ]. However, few phytochemicals have shown positive or at least similar effects to those triggered by traditional promoters on growth performance characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In such conditions animals modulate the ingestion of PBC by shifting the selection from low (e.g., leaves and cladodes) to high PBC (e.g., stems and complete plants) concentrations and vice versa [29]. Therefore, intake choices and animal ingestion behavior have direct impact in terms of bioactivity of milk and cheese [5,10,16,23]. In these farming conditions, the ability of animals to match food items varying in PBC to meet nutritional requirements is remarkable, because it must be underneath the threshold of PBC harmful intake [5,23].…”
Section: Bioactive Compounds In Vegetation Species Browsed/grazed By Goats On Semiarid Rangelandsmentioning
confidence: 99%
“…Indoor feeding instead, increased the concentration of specific PCB as ferulic acid, because maize grain, which is included in the indoor diet formulation, is a rich supply of such phytochemical. Apart from nutritional and hygienic quality, hedonic quality is a major driver of consumers food preference [56], a characteristic that would be improved by the occurrence of PBC in milk and cheese products increasing their acceptance [16]. Because of distinct PBC between milk and cheese, it is expected that consumer preference would also be shaped by this effect.…”
Section: Bioactive Compounds In Goat's Milk and Cheesementioning
confidence: 99%
See 1 more Smart Citation
“…Gorelik and Kanner [ 38 ] indicated that lipid peroxidation promotes the formation of rancid and other unpleasant odours, the oxidation of myoglobin resulting in deterioration in the colour of fresh meat. Regarding animal feed, rosemary did not significantly affect the evaluated attributes ( p ≥ 0.05), except on days 7 and 21 of storage in the case of meat odour and on day 21 for meat colour and fat colour, when the R samples presented the highest values for these attributes, this confirms the positive effect of the rosemary extract on the odour and colour of the meat [ 39 ]. Additionally, on days 7 and 14 of storage, the pigs fed with rosemary showed the lowest rancid odour value.…”
Section: Resultsmentioning
confidence: 74%